Short-term temporal changes in the spatial variability model of CO2 emissions from a Brazilian bare soil - La Scala, N.; Marques, J.; Pereira, G. T.; Cora, J. E. (Elsevier B.V., 2000)
In this work, the spatial variability model of CO2 emissions and soil properties of a Brazilian bare soil were investigated. Carbon dioxide emissions were measured on three different days at contrasted soil temperature and soil moisture conditions, and soil properties were investigated at the same points where emissions were measured. One spatial variability model of soil CO2 emissions was found for each measurement day, and these models are similar to the ones of soil properties studied in an area of 100 x 100 m. (C) 2000 Elsevier B.V. Ltd. All rights reserved.
Keywords: soil CO2 emission; soil properties; spatial variability